Pharmacological approaches to prevent vertical transmission of HIV and HBV. Issue 7 (3rd July 2022) - Zappulo, Emanuela; Giaccone, Agnese; Schiano Moriello, Nicola; Gentile, Ivan
ABSTRACT: Introduction: Mother-to-child transmission (MTCT) is mainly responsible for the global pediatric HIV and HBV epidemic. Vertical transmission can be prevented and reduced through a series of interventions at the primary healthcare level, including extensive screening of pregnant women, administration of antivirals or immune-based treatments, counselling on type of delivery and breastfeeding. Areas covered: In this narrative review, approved therapeutic options for the treatment of pregnant women living with HIV or HBV are discussed with special focus on efficacy and safety profiles of each agent or drug class examined. The search was performed using Medline (via PubMed), Web of Science, and Google Scholar to identify studies assessing vertical transmission of both HIV and HBV. Expert Opinion: Elimination of MTCT of both infections is firmly endorsed by major global commitments and the integration of tailored preventive interventions into maternal and newborn health services is of strategical importance to achieve this critical target. However, further research centered on antiviral-based and immunization trials among pregnant women is urgently needed to mitigate the risk of maternal and neonatal adverse outcomes, effectively prevent transmission to the offspring and finally eliminate the pediatric HIV and HBV epidemic, one of the key global health challenges of our time.